Pelatihan Memulai Usaha Untuk Wirausahawan Pada Remaja Mesjid Kecamatan Medan Helvetia - May Hana Bilqis Rangkuti; Abdillah Arif Nasution; Risanty Risanty; Juwita Agustrisna; Mustia Ismail (Pelita Masyarakat, 2021)
Remaja Mesjid Himpunan Muda Mudi Islam Akbaar (HIMMIA) in Medan Helvetia District consists of several youths who have the ability and skills. However, the development and fostering of an entrepreneurial spirit is still not optimal because the level of education of most of the target audience is high school graduates who rarely or may never receive entrepreneurship knowledge and education. Many potential creative ideas for running a business have not been explored optimally. For this reason, it requires entrepreneurial knowledge and skills that have been initiated from a young age so that it can increase entrepreneurial skills which become the basic capital for someone who wants to be engaged in certain business fields. Entrepreneurial ability is not due to the talent factor, but will also arise and be felt through entrepreneurial experiences and trainings. Therefore, it is important to do counseling about entrepreneurship among the young generation of the HIMMIA Mosque, Medan Helvetia Subdistrict, so that their orientation is no longer as job seekers, but as job creators.